Estimation of renal function in patients with diabetes - Rigalleau, V.; Beauvieux, M.-C.; Gonzalez, C.; Raffaitin, C.; Lasseur, C.; Combe, C.; Chauveau, P.; De la Faille, R.; Rigothier, C.; Barthe, N.; Gin, H. (Diabetes & metabolism, 2011)
Diabetes is the leading cause of chronic kidney disease (CKD), which makes estimation of renal function crucial. Serum creatinine is not an ideal marker of glomerular filtration rate (GFR), which also depends on digestive absorption, and the production of creatinine in muscle and its tubular secretion. Formulas have been devised to estimate GFR from serum creatinine but, given the wide range of GFR, proteinuria, body mass index and specific influence of glycaemia on GFR, the uncertainty of these estimations is a particular concern for patients with diabetes. The most popular recommended formulas are the simple Cockcroft–Gault equation, which is inaccurate and biased, as it calculates clearance of creatinine in proportion to body weight, and the MDRD equation, which is more accurate, but systematically underestimates normal and high GFR, being established by a statistical analysis of results from renal-insufficient patients. This underestimation explains why the MDRD equation is repeatedly found to give a poor estimation of GFR in patients with recently diagnosed diabetes and is a poor tool for reflecting GFR decline when started from normal, as well as the source of unexpected results when applied to epidemiological studies with a 60mL/min/1.73m2 threshold as the definition of CKD. The more recent creatinine-based formula, the Mayo Clinic Quadratic (MCQ) equation, and the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) improve such underestimation, as both were derived from populations that included subjects with normal renal function. Determination of cystatin C is also promising, but needs standardisation. Le diabète est une cause majeure d’atteinte rénale, estimer la fonction rénale des patients diabétiques est donc crucial. La créatininémie n’est pas un marqueur idéal du débit de filtration glomérulaire (DFG), car elle dépend aussi de l’absorption digestive et de la production musculaire de créatinine, ainsi que de sa sécrétion tubulaire. Des équations intégrant des données anthropométriques doivent donc être utilisées pour estimer le DFG, avec des incertitudes particulières pour les patients diabétiques du fait du large éventail de DFG, de protéinurie, d’index de masse corporelle, et de l’effet propre de la glycémie. Les plus utilisées et recommandées sont la formule de Cockcroft-Gault, simple mais peu précise et biaisée car elle estime la clairance de la créatinine comme proportionnelle au poids, et l’équation de la MDRD, plus précise mais qui sous-estime les DFG normaux car elle a été établie à partir d’une population d’insuffisants rénaux. Cette sous-estimation explique ses mauvaises performances pour estimer le DFG dans des groupes de patients diabétiques récents pour estimer le déclin du DFG en partant de valeurs normales, et aussi certains résultats inattendus d’études épidémiologiques ayant utilisé le seuil de 60mL/min/1,73m2 pour définir l’atteinte rénale. La sous-estimation est moindre avec les équations plus récentes (Mayo Clinic Quadratic, CKD-EPI) qui ont été établies à partir de populations incluant des sujets sans insuffisance rénale. La cystatine C est aussi un progrès pour l’estimation du DFG mais nécessite une standardisation.